Macrophage Regnase-1 Deletion Deteriorates Liver Ischemia/Reperfusion Injury Through Regulation of Macrophage Polarization - Xiaoming, Ai; Wenbo, Jia; Jinyi, Wang; Bin, Wu; Chunyang, Hu; Qi, Chen; Lianbao, Kong (Frontiers in Physiology, 2020)
Background: Regnase-1 (MCPIP) has been identified as an anti-inflammatory agent, but little is known about its influence on liver ischemia/reperfusion (I/R) injury. Macrophages can evolve biphasic responses and differentiate into remarkable polarizations, contributing greatly to the uncontrolled inflammatory cascades during liver I/R injury. Therefore, the aim of this study was to explore whether regnase-1 participated in liver I/R via manipulating macrophage polarization. Materials and methods: C57BL/6 mice were randomly divided into five groups: Sham, I/R, Clodronate, Clo+ BMDM, and Clo+ LV MCPIP BMDM. A liver I/R model was established, and histopathological and immunostaining examinations were performed for the liver specimens, and double immunofluorescence staining was used to localize MCPIP in the liver. Primary hepatocytes were isolated to simulate H/R model in vitro. BMDM were extracted and subjected to lentiviral transduction to knock down MCPIP expression. BMDM with or without MCPIP deletion were exposed to H/R supernatants, and the polarized states were measured by flow cytometry. RT-PCR analysis and Western blot were also conducted. Results: Compared to those in the Sham group, liver functions and Suzuki’s scores were deteriorated in the I/R group, which were reversed in the Clodronate group. The increased expression of regnase-1 in the I/R group diminished with pretreatment of clodronate liposomes. Subsequent double immunofluorescence staining established the localization of regnase-1 in macrophages in the liver. The insulted lesions in the Clodronate group became progressively aggravated with adoptive transfer of BMDM in the Clo+ BMDM group, which were more exacerbated with transfusion of BMDM with MCPIP knockdown in the Clo+ LV MCPIP BMDM group. Gene expressions of M1 and M2 markers were detected by RT-PCR, suggesting that MCPIP knockdown tended to favor the M1 transformation. Subsequently, ex vivo flow cytometrical detection showed that upon stimulation by H/R supernatants, LV-MCPIP BMDM posed a higher ratio of M1/M2 than BMDM. Finally, we testified that MCPIP participated in macrophage M1/M2 polarization through the NF-κB and C/EBPβ and PPARγ signaling pathway during liver I/R. Conclusion: Our study confirmed that regnase-1 played a critical role in liver I/R via regulation of macrophage polarization, and thus, might offer a potential therapeutic target.